2017
DOI: 10.1039/c7ra04021k
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature solution-processed MoOx as hole injection layer for efficient quantum dot light-emitting diodes

Abstract: In this work, quantum dot light-emitting diodes (QD-LEDs) based on a low-temperature solution-processed MoOx hole injection layer were fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…40 It is important to point out that the value displayed for the work function of MoO x in the diagram of Figure 1d was extracted from a few reports on the literature dealing solution-processed MoO x , used as reference. [28][29][30] Nevertheless, it has been shown that work function of MoO x might significantly vary upon temperature annealing, 41,42 oxygen/air exposure, 17,42 and also with film thickness, 14,17 so very different values, ranging from 6.8 eV up to -4.9 eV, have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 It is important to point out that the value displayed for the work function of MoO x in the diagram of Figure 1d was extracted from a few reports on the literature dealing solution-processed MoO x , used as reference. [28][29][30] Nevertheless, it has been shown that work function of MoO x might significantly vary upon temperature annealing, 41,42 oxygen/air exposure, 17,42 and also with film thickness, 14,17 so very different values, ranging from 6.8 eV up to -4.9 eV, have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the mechanism by which the MoO x film enabled the highest diode performance cannot be explained simply by morphology effects on the emissive polymer layer. For OLEDs, QLEDs and PLEDs containing other polymers than the one used here, it has been proposed that incorporation of MoO x contributes to enhance diode performance through the following ways: reduction of holeinjection barrier due to the high work function of this metal oxide; 10,40,41,53 enhanced hole transport, 54 thus improving charge carrier balance; reduction of the efficiency roll-off typically observed when using PEDOT:PSS; 41 and enhanced operational stability. 30,40,41 A thorough investigation of the electrical and electronic properties of the MoO x films used in this work to better understand their role in enhancing the PFO-based PLED performance is being conducted and will be reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the acidity makes it easy to corrode the ITO anode, which affects the performance of the device. In order to overcome this problem, researchers try to use some other substitutes, and thus some classic material such as molybdenum trioxide (MoO3), vanadic oxide (V2O5) and tungsten trioxide (WO3) have been developed [3][4][5][6][7]. However, these materials show some similar properties more or less, and the performance of the prepared devices has not been significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…PEDOT:PSS, a common hole injection layer (HIL), has a high electrical conductivity, high optical transparency, and smooth morphology, but it is highly acidic, which can cause erosion of the anode (indium‐tin‐oxide: ITO), resulting in reduced lifetime of QLED devices . To overcome this issue, new hole injection materials such as graphene oxide (GO), and transition metal‐oxides have been intensively studied as an alternative HIL replacing PEDOT:PSS. Examples of typical transition metal‐oxides for HIL include vanadium oxide (V 2 O 5 ), nickel oxides (NiOx), molybdenum oxide (MoO 3 ), and tungsten oxide (WO 3 ) …”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, new hole injection materials such as graphene oxide (GO), and transition metal‐oxides have been intensively studied as an alternative HIL replacing PEDOT:PSS. Examples of typical transition metal‐oxides for HIL include vanadium oxide (V 2 O 5 ), nickel oxides (NiOx), molybdenum oxide (MoO 3 ), and tungsten oxide (WO 3 ) …”
Section: Introductionmentioning
confidence: 99%